The learner-centered curriculum: Is it the missing piece in coaching programs? - Martins, L. C.; Woodburn, A. J.; Milistetd, M. (International Sport Coaching Journal, 2025)
Sports federations and national sports organizations worldwide are responsible for coaching education programs. While notable progress has been made to improve the quality of coaching in different countries over the past two decades, the literature still highlights limitations in coach education programs regarding the achievement of meaningful learning. A learner-centered perspective that promotes ongoing development is suggested instead of a traditional instructional approach to overcome this. However, shifting to adopting a learner-centered curriculum remains a challenge. Although evidence of the paradigm shift exists within the microcontext of teaching and learning, researchers highlight the difficulty of application of a learner-centered culture in coach education. This article examines the traditional curriculum`s conception and design, the need for restructuring, and the principles of learner-centered curricular design. Additionally, it provides practical implications to assist sports organizations in creating a learner-centered curriculum.